2018
DOI: 10.1111/and.13005
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of daily use of tadalafil in treatment of patients with premature ejaculation: A randomised placebo‐controlled clinical trial

Abstract: The study aimed to evaluate the efficacy and safety of the once-daily use of 5 mg tadalafil in the treatment of patients with premature ejaculation (PE). In a single-blind placebo-controlled clinical study, it was carried out on 100 patients with PE. All patients were randomised equally divided into two groups (50 patients each). Group 1 was given placebo in the form of oral multivitamin tablet once a day for 6 weeks. Group 2 was given 5 mg tadalafil once a day for 6 weeks. All patients were asked to complete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 24 publications
(28 reference statements)
1
9
0
Order By: Relevance
“…Eleven studies were excluded without useful data. Totally, seven (Abu El-Hamd, 2018; Abu El-Hamd & Abdelhamed, 2018; Atan et al, 2006; Aversa et al, 2009; Gameel et al, 2013; Mattos et al, 2008; McMahon et al, 2005) placebo-controlled studies were included in the meta-analysis. One study (Atan et al, 2006) only contained the data about the safety of PDE5Is.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eleven studies were excluded without useful data. Totally, seven (Abu El-Hamd, 2018; Abu El-Hamd & Abdelhamed, 2018; Atan et al, 2006; Aversa et al, 2009; Gameel et al, 2013; Mattos et al, 2008; McMahon et al, 2005) placebo-controlled studies were included in the meta-analysis. One study (Atan et al, 2006) only contained the data about the safety of PDE5Is.…”
Section: Resultsmentioning
confidence: 99%
“…The indicators IVELT and score of sexual satisfaction scale were used to assess the efficacy of PDE5Is in the treatment of PE. Six studies (Abu El-Hamd, 2018; Abu El-Hamd & Abdelhamed, 2018; Aversa et al, 2009; Gameel et al, 2013; Mattos et al, 2008; McMahon et al, 2005) including 431 patients compared the indicator IVELT and 3 (Abu El-Hamd & Abdelhamed, 2018; Gameel et al, 2013; McMahon et al, 2005) RCTs (261 patients) compared the score of sexual satisfaction scale between the group treated with PDE5Is and that treated with placebo. According to the analysis, patients who were treated with PDE5Is had significantly increased IVELT compared with those treated with placebo.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a single-blind placebo-controlled study, usage of singledose 5 mg tadalafil daily for six weeks has been shown to be effective and well-tolerated in the treatment of premature ejaculatory patients [13] . In another study, in a significant percentage of patients after using chronic tadalafil for six months, a reduction in sexual function changes, such as premature ejaculation, was observed [14] .…”
Section: Discussionmentioning
confidence: 99%